Implementasi Rencana Kontinjensi Nuklir Reaktor Riset Dalam Upaya Kesiapsiagaan Nuklir - Aprialiani, Dewi; Kerta Widana, I Dewa Ketut (Republic of Indonesia Defense University, 2019)
Indonesia has three nuclear research reactors, nemely: RSG-GAS in Serpong, TRIGA2000 reactor in Bandung, and Kartini reactor in Yogyakarta. Besides being useful, nuclear reactor has inharent risk due to its radiation hazard. The research reactor nuclear contingency plan was prepared for nuclear preparedness. The study aimed to analyze the implementation of the research reactors’ nuclear contingency plans. The study used an analytic descriptive qualitative methods. The results showed that the nuclear contingency plans of the three research reactors have different implementation range due to their different hazard risks. However, the nuclear emergency responses were the same, they were: sheltering, evacuation, provision of KI tablets, and prohibition of consumption of local food and contaminated river/ ground water. The research reactors’ nuclear contingency plans have not discussed criteria used for taking nuclear emergency responses. The results also showed that the nuclear contingency plan of RSG-GAS in Serpong and the Kartini reactor in Yogyakarta have been implemented partially. While for the TRIGA2000 reactor nuclear contingency plan in Bandung has not been implemented yet. A legal umbrella is needed to implement the research reactor nuclear contingency plan. Thus, coordination and active role from all stakeholders are needed to be enhanced in order to be able to resolve the existing obstacles and challenges.